A New Gen IoT Cloud Platform Benefits and Challenges - Rashmi Rao K (International Journal of Advanced Science and Technology, 2020)
IoT cloud platform generates abilities to  IoT gadgets and CC Provides a assistance over an end-to-end customer requirements and  implied by other publicizing factors such as a  IoT Cloud  Platform. In this era, where billions of e-gadgets are connected via Internet, we see growing potential of striking big data obtained from these e-gadgets and operating them thoroughly through various implementations. IoT Gadgets are e-gadgets with countless sensors connected to the cloud, classically via gateways. There are many IoT Cloud Podiums in the business today provided by various service providers that host broad ranging services. This paper tells about Different Architecture of IoT Cloud Platforms and its Benefits and challenges.